Third-order optical nonlinearity in nucleobase solid thin solid film and its application for ultrashort light pulse generation. Issue 9 (8th February 2022) - Khazaeinezhad, Reza; Kassani, Sahar Hosseinzadeh; Ghasemi, Marjan; Cho, Yongjae; Il Im, Seong; Il Yeom, Dong; Rotermund, Fabian; Grote, James G; Deleporte, Emmanuelle; Ledoux-Rak, Isabelle; Oh, Kyunghwan
Abstract : Generating high stability ultrafast pulse laser using constituents of the most powerful biomolecules in nature (Adenine, Guanine, Cytosine, and Thymine). Abstract : Adenine, Guanine, Cytosine, and Thymine are the fundamental constituents of DNA and RNA, the building blocks of living organisms. We revealed these nucleobases' nonlinear optical properties in solid thin films and successfully applied them for ultrashort laser pulse generation. Nucleobase thin solid films were fabricated by using the organic molecular beam deposition process, and Z -scan measurements confirmed their high third-order optical nonlinearity. Nucleobase thin solid films were further deposited on a side-polished silica optical fiber, which served as an all-fiber saturable absorber in a ring laser cavity. We generated stable transform-limited femtosecond soliton pulse trains in the anomalous dispersion regime using an Erbium-doped fiber as a gain medium. These new findings of optical nonlinearities in nucleobase thin solid film can open a new avenue of photo-metrology, taking advantage of integration capability and bio-compatibility.